Gambaran Pengetahuan Wanita Usia Subur Terhadap Kejadian Keputihan - Fera Ulfah Pernanda; Ledy Octaviani Iqmy; Devi Kurniasari (MIDWIFERY JOURNAL, 2026)
Backround: Vaginal discharge (fluor albus) is one of the most common reproductive complaints experienced by women of childbearing age. This condition can be physiological or pathological and is often influenced by hygiene and individual knowledge. Lack of understanding  can cause women to be unable to distinguish between normal and abnormal conditions, putting them at risk of infections that affect their reproductive health.Purpose: This study aims to determine the knowledge of women of childbearing age regarding vaginal discharge at the Kebon Jahe Community Health Center in Bandar Lampung in 2025.Methods:  The  study  used  a  quantitative  descriptive  design  with  a  cross-sectional  approach.  The  sampleconsisted of 30 female respondents of childbearing age who were selected using total sampling technique. The research instrument was a closed questionnaire containing 20 questions. The data were analyzed univariately for frequency distribution and univariate analysis.Result: The results showed that the majority of respondents had a high school education (90%). A total of 29 respondents (97%) had good knowledge, while 1 respondent (3%) had poor knowledge.Conclusion: For health workers to maintain educational programs for adolescent girls on maintaining genital hygiene to prevent vaginal discharge. Furthermore, this study can be used as data for future researchers, who are expected to take larger samples that are representative of the existing population using a qualitative approach in order to gain a deeper understanding of adolescent girls' behavior in maintaining genital hygiene to prevent vaginal discharge. Keywords : Knowledge, Women of Childbearing Age, Vaginal Discharge ABSTRAK Latar belakang: Keputihan (fluor albus) merupakan salah satu keluhan reproduksi yang paling sering dialami wanita usia subur. Kondisi ini dapat bersifat fisiologis maupun patologis dan sering dipengaruhi oleh faktor kebersihan serta pengetahuan  individu.  Kurangnya  pemahaman    dapat menyebabkan wanita tidak  mampu membedakan kondisi normal dan abnormal, sehingga berisiko mengalami infeksi yang berdampak pada kesehatan reproduksi.Tujuan: Penelitian ini bertujuan untuk mengetahui gambaran pengetahuan wanita usia subur mengenai kejadian keputihan di Puskesmas Kebon Jahe Bandar Lampung tahun 2025Metode:  Penelitian  menggunakan  desain  deskriptif  kuantitatif  dengan  pendekatan  cross-sectional.  Sampel berjumlah 30 responden wanita usia subur yang dipilih dengan teknik total sampling. Instrumen penelitian berupa kuesioner tertutup berisi 20 pertanyaan. Data dianalisis secara univariat untuk distribusi frekuensi dan univariat. Hasil: penelitian menunjukkan mayoritas responden berpendidikan SMA (90%). Sebanyak 29 responden (97%) memiliki pengetahuan baik, sementara 1 responden (3%) berpengetahuan kurang.Bagi  tenaga  kesehatan  untuk  mempertahankan  program  penyuluhan  kepada  remaja  putri  tentang  perilakumenjaga kebersihan organ genitalia dalam mencegah keputihan. Dan bagi peneliti selanjutnya dapat dijadikan sebagai data untuk peneliti selanjutnya, di-harapkan dapat mengambil sampel yang lebih besar dan mewakili populasi yang ada dengan menggunakan pendekatan kualitatif agar dapat lebih mendalam mengetahui per-ilaku remaja putri tentang menjaga kebersihan organ genitalia dalam mencegah keputihan. Kata Kunci : Pengetahuan, Wanita Usia Subur, Keputihan